แนวทางการตีความ คำว่า "อุบัติเหตุ" กรณีความรับผิดของผู้ขนส่งต่อคนโดยสาร ในการรับขนระหว่างประเทศทางอากาศ - เกิดกันยา ธำรงสิริภาคย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
The objective of this thesis is to illustrate on the interpretation guideline of the term "accident" under carrier’s liability for passengers in case of international carriage by air. The term "accident" stipulated in Article 17 of the Convention for the Unification of Certain Rules or Montreal Convention 1999 is the core requirement to liability of carrier for passenger death and injury. However, the convention did not provide clear definition regarding this term. Inconsistency of the law has emerged, since every court of the signatory State has a different jurisdiction and interpret the term individually. This might cause confusion in the international air transport community, which will impact to both air carriers and passengers, and eventually leading to an inconsistent uniformity of the rules on international aviation. Due to the lack of an unequivocal term issue, it is necessary to study on the interpretation guideline of the term "accident" in order for the carriers and passengers to understand their right duty and liability, most importantly is to achieve a uniform interpretation, which is the purpose of the Convention. The study renders that the term "accident" should be observed and interpreted in accordance with the interpretation of treaties rules provided by Vienna Convention on the Law of Treaties 1969 Articles 31 and 32, in respect of textual basis, context and preparatory work, including considering the interpreted cases by signatory States. It is worth mentioning that in case of Thailand, the term "accident" of section 10 International Carriage by Air Act B.E. 2558, should be interpreted as a technical term in the light of Montreal Convention 1999 and International Carriage by Air Act B.E. 2558 purpose. Also, it shall be construed together with the text, context, and preparatory work of both Montreal Convention and International Carriage by Air Act B.E. 2558. And determine the proper definition of the term by studying valuable interpreted cases by signatory States.